Testing of One-Row Rice Reaper - Djojowasito, Gunomo; Ahmad, Ary Musthofa; Wicaksono, Ronny (Fakultas Teknologi Pertanian Universitas Brawijaya, 2002)
Harvesting is one of the critical operations in the rice cultivation. It need to be handled properly so it can reduce grain losses and then lead to an increase in total rice production. One of that method is by applying agricultural machinery, in this case is one-row rice reaper. This study is conducted to identify the performance of the reaper especially the field capacity and effectiveness of cutting. Thus it can be compared to that manual one. The result shows that the reaper is able to cut properly, but it need further study on the side-delivery function of cut plant. The field capacity of the reaper is greater then the traditionally manual one. It also needs more development to improve its mobility on the field. Â Keywords: one-row rice reaper, harvesting, agricultural machinery